PROTOTYPE EFFECTS AND CATEGORY EXTENSION IN THE POLYSEMY OF SCIENTIFIC LEXIS (Web of Teachers: Inderscience Research, 2025)
Scientific terms seldom remain monosemous: as disciplines evolve, new experimental settings and interdisciplinary transfers generate additional senses. Drawing on cognitive-linguistic notions of prototypicality and radial category structure, this article investigates how prototype effects constrain – and category-extension mechanisms enlarge – the polysemy of 120 high-frequency terms from physics, biochemistry, and artificial-intelligence research published between 2015 and 2024. A mixed corpus-driven and psycholinguistic method reveals (i) a stable prototype sense that anchors each term, (ii) three dominant extension routes (metaphor, metonymy, operational re-definition), and (iii) a measurable “semantic detoxification” process that reconciles old and new meanings. The proposed typology clarifies why scientific communities can share terminology across fields without losing precision and offers guidelines for terminographers and translators.